2017
DOI: 10.1002/yea.3247
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide map of Apn1 binding sites under oxidative stress in Saccharomyces cerevisiae

Abstract: The DNA is cells is continuously exposed to reactive oxygen species resulting in toxic and mutagenic DNA damage. Although the repair of oxidative DNA damage occurs primarily through the base excision repair (BER) pathway, the nucleotide excision repair (NER) pathway processes some of the same lesions. In addition, damage tolerance mechanisms, such as recombination and translesion synthesis, enable cells to tolerate oxidative DNA damage, especially when BER and NER capacities are exceeded. Thus, disruption of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This analysis indicated that furfuralinduced DSBs that initiated mitotic recombination occur more frequently in GC-rich regions. In cells, repair of oxidized bases through the base excision repair pathway generates apurinic/apyrimidinic (AP) sites that can be removed by backbone cleavage, end processing, DNA synthesis, and ligation (39,40). Two recent studies showed, through analysis of the distributions of AP sites across the genome, that oxidative damage accumulates preferentially in GC-rich regions (39,40).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis indicated that furfuralinduced DSBs that initiated mitotic recombination occur more frequently in GC-rich regions. In cells, repair of oxidized bases through the base excision repair pathway generates apurinic/apyrimidinic (AP) sites that can be removed by backbone cleavage, end processing, DNA synthesis, and ligation (39,40). Two recent studies showed, through analysis of the distributions of AP sites across the genome, that oxidative damage accumulates preferentially in GC-rich regions (39,40).…”
Section: Figmentioning
confidence: 99%
“…In cells, repair of oxidized bases through the base excision repair pathway generates apurinic/apyrimidinic (AP) sites that can be removed by backbone cleavage, end processing, DNA synthesis, and ligation (39,40). Two recent studies showed, through analysis of the distributions of AP sites across the genome, that oxidative damage accumulates preferentially in GC-rich regions (39,40). Because incision of close AP sites would give rise to DSBs (25), repair of oxidized bases within GC-rich regions may be a factor that contributes to mitotic recombination in furfural-treated cells.…”
Section: Figmentioning
confidence: 99%